2021
DOI: 10.1186/s13018-021-02420-7
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous, PMMA-augmented, pedicle screw instrumentation of thoracolumbar ankylotic spine fractures

Abstract: Introduction Fractures in the ankylotic spine may have an insidious presentation but are prone to displace with devastating consequences. The long lever arm of ankylosed spine fragments may lead to pulmonary and great vessel injury and is difficult to adequately immobilize. Conservative treatment will produce in many cases poor outcomes with high morbidity and mortality. Open surgical treatment is also fraught with technical difficulties and can lead to major blood loss and prolonged operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…The clinical outcomes of our robot-assisted percutaneous xation technique are consistent with previous studies on minimally invasive surgery, demonstrating consistently favorable results [12,30,31]. The VAS and ODI values were 1.3 ± 1.0 and 11.8 ± 6.6%, respectively, at the most recent follow-up.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The clinical outcomes of our robot-assisted percutaneous xation technique are consistent with previous studies on minimally invasive surgery, demonstrating consistently favorable results [12,30,31]. The VAS and ODI values were 1.3 ± 1.0 and 11.8 ± 6.6%, respectively, at the most recent follow-up.…”
Section: Discussionsupporting
confidence: 85%
“…Barkay et al [39] demonstrated that postponing surgical intervention (> 72 hours) in elderly patients with spinal ankylosing disorders may lead to an increase in medical complications and mortality. In our study, surgery was delayed in 8 (67%) patients; however, no patients died, and the incidence of postoperative complications was 8.3%, which was lower than that reported in other studies [12,30,39]. This could potentially be attributed to the limited sample size of participants in our research or the use of robot-assisted technology, which improves work e ciency and promotes early rehabilitation.…”
Section: Discussioncontrasting
confidence: 64%
“…Several case series have found that percutaneous instrumentation among patients with thoracolumbar fractures and underlying AS provide sufficient radiographic alignment without loss of reduction or need to convert to open surgery and provide similar clinical outcomes to open surgery 11,14,1720 . Previous studies have also shown that percutaneous pedicle screw placement provides multiple benefits including decreased blood loss, decreased risk of infection, decreased paraspinal muscle damage, and decreased length of hospital stay (Table I) 2128 . A meta-analysis comparing open versus minimally invasive techniques in thoracolumbar trauma found equivalent results in clinical and radiographic outcomes, with the advantage of decreased intraoperative blood loss and operative times offered by minimally invasive surgery 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, minimally invasive surgery has been recognized by the majority of doctors, especially for elderly AS patients with more underlying diseases. It can achieve better clinical results and reduce the occurrence of surgical complications [ 9 , 10 , 29 , 30 ]. Ye et al [ 9 ] demonstrated that minimally invasive surgery can achieve effects similar to those of traditional open surgery, while reducing bleeding, trauma, and postoperative complications.…”
Section: Discussionmentioning
confidence: 99%